PCR-based diagnosis and clinical insights into parasitic keratitis - Suan Hwang; I-Huang Lin; Chun-Chieh Lai; Fu-Chin Huang; Sung-Huei Tseng; Yi-Chen Chen; Chung-Han Ho; Wei-Chen Lin; Yi-Hsun Huang (Journal of Microbiology, Immunology and Infection)
Purpose: This retrospective study aimed to investigate demographic characteristics, predisposing factors, and clinical outcomes in patients with parasitic keratitis. Methods: Medical records of patients with molecularly confirmed Acanthamoeba or microsporidia, identified through corneal scraping specimens (collected between September 21, 2017, and June 27, 2023), were reviewed. Demographic data, clinical profiles, such as symptom duration before confirmed diagnosis, antiviral treatment pre-diagnosis, contact lens use, tap water and soil contamination, ocular trauma, and treatment regimens, were analyzed. Results: Fifty PCR-confirmed cases included 35 Acanthamoeba keratitis (AK) and 15 microsporidia keratitis (MK). Of these, 23 males and 27 females, aged 8 to 81, showed a significant difference (p = 0.02) in the distribution of farmers between the AK and MK groups. Mean symptom durations pre-diagnosis were 27.6 days (range: 1–180) in AK and 11.47 days (range: 1–60) in MK. AK cases exhibited a higher prevalence of stromal involvement (p < 0.05) and contact lens use (p < 0.001), while more MK patients had a history of soil contamination (p = 0.016). Univariable analysis linked stromal keratitis, symptom duration, and pre-diagnosis antiviral treatment to prolonged time to stability. In the multivariable model, only symptom duration predicted extended time to stability, with an expected increase of 0.65 days for each additional pre-diagnosis day. Conclusion: This study underscores the significance of parasitic keratitis in Southern Taiwan, emphasizing the necessity of incorporating PCR as an effective diagnostic tool to enhance the routine identification of these rare conditions, moving beyond reliance on standard conventional methods.